Menumbuhkan Kepedulian Pelajar SMA YSP PUSRI Palembang Terhadap Keberlangsungan Energi Listrik Melalui Gerakan Hemat Energi dan Pemanfaatan Solar Sel - Oktaviani, Wiwin Armoldo; Danus, Muhardanus; Noveriyanti, Rika (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
YSP PUSRI Senior High School  is a school under the auspices of the Yayasan Sosial Pendidikan Pupuk Sriwijaya. The average students of this school come from the upper middle class. Therefore, most of the students are very familiar with all the ease of activities and comfort because they supported by a variety of electronic equipment. In addition, as a Adiwiyata winning school in the province of South Sumatra, this school implements a Green Ecology policy by using solar cells as an energy source for lighting. On the other hand, students' awareness of the importance of saving electricity is still low. For them, saving electricity is synonymous with reducing their comfort and pleasure. Therefore, with this condition it is deemed necessary to conduct extension activities in order to provide knowledge to students, about how to use and maintain safe and economical electrical equipment and how to apply energy solar cells as an effort to maintain the sustainability of electrical energy in Indonesia